"Our inherent desire for control": a case study of automation's impact on the perception of comfort. (September 2017) - Brambilla, Arianna; Alavi, Hamed; Verma, Himanshu; Lalanne, Denis; Jusselme, Thomas; Andersen, Marilyne
Abstract: To investigate the relationship between occupants' perception of control over building elements and their comfort, we conducted a study where two prototype office rooms were compared: while the first room allowed occupants to open or close the window and configure the shading, the second one was fully automated. The quantitative analysis of collected data a) supports the existing results in the literature reporting higher satisfaction where manual control is maintained, and b) uncovers a new impact of highly automated systems: lower control over building elements can increase the occupant's consciousness of the environmental factors and the saliency of comfort parameters.